Energiomstilling av bolig kan bli en netto kostnad for gjennomsnittshusholdningen - Haakon Solheim; Bjørn Helge Vatne (Norges Bank, 2024)
– Energy consumption in homes accounts for over 30 percent of annual Norwegian electricity consumption. The government has set targets to reduce energy consumption in the housing sector. Measures that can increase energy efficiency in the housing sector are both known and available, but they will require significant investment. Based on estimated energy consumption per home, we analyse the ability of Norwegian homeowners to finance stricter energy efficiency requirements without public support. The estimate is based on information about homeowners' income, debt and wealth and on homes' estimated current electricity consumption, size and type. We find that around 10 percent of homeowners do not have the financial means to implement the energy efficiency measures required to comply with the requirements. The measures result in lower electricity expenses, but at current interest rates and electricity prices, there is reason to believe that such energy efficiency improvements will be a net cost for the average household. To assess these costs, access to detailed information about a home's energy consumption is key. If energy efficiency improvements are to be debt-financed, this will increase demand for new loans.
hdl:11250/3170058
Keywords: 330; Climate policy; House prices; Household finances; Energy efficiency